Perubahan Morfologi Sungai Lariang: Analisis Spasiotemporal dengan Pendekatan Penginderaan Jauh - Awaluddin, Ahmad Reski; Maskur, Nur Fitriani; Abdurrahman, Hadi; Munaja, Rahmiyatal (Prodi PWK Universitas Tadulako, 2025)
Rivers are one of the natural elements that play an important role in the ecosystem, both in terms of water supply, agricultural irrigation, and supporting biodiversity.The continuously changing morphology of the river needs to be monitored periodically to understand the dynamics of changes and their impact on the environment.This study aims to identify the dynamics of morphological changes in the lower reaches of the Lariang River based on river erosion and deposition over a 10-year period.The method used is spatiotemporal analysis of river erosion and deposition patterns in 2013, 2018, and 2023. The analysis was conducted through the interpretation of Google Earth Pro satellite imagery, which was then digitized using ArcGIS software.The research results indicate that there are significant dynamics in the river meanders at several points, especially in segments with sharp bends.During the period 2013-2018, the area of erosion was 971,298 m², while the area of accretion was 1,624,959 m².In the period 2018-2023, the area of erosion was 644,619 m², while the area of accretion was 981,088 m².The high dynamics of erosion and accretion cause river deflection and the formation of new landforms.